Renormalized solutions of non-linear elliptic problems with three lower-order terms and -data. (June 2017) - Benkirane, A.; Moumni, M. El; Fri, A.
Abstract: We prove the existence of a renormalized solution in Sobolev spaces for a class of non- linear elliptic equations with lower- order terms and -data.